The functional and clinical significance of nucleoporin NUP153 across human cancers: a systematic study based on multi-omics analysis and bench work validation - He, Youfu; Wang, Qing; Wang, Zhaorui; Duan, Menghui; Zhou, Yu; Huang, Jing; Wu, Qiang; Wu, Feichang; Li, Chen (Frontiers in Immunology, 2025)
BackgroundCancer is a group of highly heterogeneous malignant diseases, and early diagnosis plays a crucial role in improving patient outcomes. Nucleoporins, including Nucleoporin (NUP)153, are involved in key cellular processes such as nucleocytoplasmic transport and cell cycle regulation. However, the role of NUP153 in cancer, especially its expression patterns, mutations, diagnostic value, and relationship with the tumour immune microenvironment, remains insufficiently explored.MethodsThis study analysed NUP153 expression data from public databases such as TCGA and GTEx. Expression differences between tumour and normal tissues were assessed using Wilcoxon signed-rank tests. Gene set enrichment analysis (GSEA) was used to identify the biological functions and pathways related to NUP153. The relationship between NUP153 expression and immune cell infiltration was evaluated using the TIMER database, while drug sensitivity data were obtained from the GDSC and CTRP databases. Additionally, NUP153 expression in gastric cancer tissues was validated using immunohistochemistry and RT-qPCR.ResultsNUP153 showed significant expression variation across cancers, with high levels in cholangiocarcinoma, colorectal cancer, and head and neck squamous cell carcinoma. In gastric cancer, NUP153 was markedly upregulated compared to adjacent non-cancerous tissues. High NUP153 expression was linked to tumour-associated macrophage infiltration and correlated with poor prognosis in some cancers like Kidney Renal Papillary Cell Carcinoma and Sarcoma. Drug genomics analysis revealed that NUP153 expression predicted chemotherapy resistance, with imatinib and 4.5-dianilinophthalimide showing potential for inhibition in multiple cancers. Single-cell analysis and spatial transcriptomics further revealed that NUP153 expression drives proliferative states in mucus-producing cells in gastric cancer, and its expression was associated with immune cell infiltration patterns, particularly neutrophil and macrophage distribution in the tumour microenvironment.ConclusionOur findings indicate that NUP153 is a critical factor in multiple cancers, especially gastric cancer, where its elevated expression holds promise as a diagnostic and prognostic biomarker. The results indicate that NUP153 plays a key role in modulating the immune microenvironment and driving tumour progression, positioning it as a potential target for future therapeutic interventions. However, additional studies are required to elucidate the specific molecular mechanisms underlying NUP153’s function in cancer and to explore its clinical applicability.